Estudo da caracterização mecânica de flexão em compósitos cimentícios reforçados com fibras de malva - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The present research involves production and characterization of cementitious composites with pozzolan addition reinforced with mauve fibers, arranged in the form of short fibers (disoriented) with 2% volume and long fibers (oriented in one direction) for volumes of 6%, 8% e 10%. Natural fibers are very interesting in the field of scientific research, and promotes the concept of sustainability. Its improve the mechanical performance of cementitious composites when used properly applied as reinforcemente. Therefore, the development of a cement matrix with calcium hydroxide reduction through the incorporation of calcined clay, which is a metakaolin from kaolin from the Amazon region, intends to avoid the deterioration of the reinforcement employed. The composites produced were mechanically tested by four point bending test. Laminates with 10% of treated long fibers have higher ductility than the other laminates produced, which is confirmed by the multiple cracking behavior and also an equivalent flexural stress higher, which averages 43MPa. While the most fragile composite reached an average of 12MPa, for 2% volume of short fibers, besides presenting sudden rupture, without significant amounts of visible cracks.
Keywords: Compósitos cimentícios; Metacaulinita; Fibras naturais; Fibras de Malva; Pozolana; ENGENHARIAS: ENGENHARIA CIVIL; Malva; Fibras naturais; Metacaulinita; Compósitos cimentícios